Case report: Treatment of long COVID with a SARS-CoV-2 antiviral and IL-6 blockade in a patient with rheumatoid arthritis and SARS-CoV-2 antigen persistence - Visvabharathy, Lavanya; Orban, Zachary S.; Koralnik, Igor J. (Frontiers in Medicine, 2022)
Introduction: Long COVID, or post-acute sequelae of SARS-CoV-2 infection (PASC) in 30% of all infected individuals. Here, we present a case of PASC in a patient with rheumatoid arthritis characterized by viral persistence in the nasopharynx for 6 months after acute infection. We demonstrate transient disappearance of antigen persistence and decreased antiviral and autoimmune T cell responses after nirmatrelvir/ritonavir and tocilizumab treatment. Case Presentation: A 37-year-old female with a 7-year history of rheumatoid arthritis enrolled in a COVID-19 research study was found to continuously test SARS-CoV-2 antigen positive in the nasopharynx for 6 months after acute infection. She simultaneously presented with new-onset PASC symptoms including chronic occipital headache and periods of intense fatigue 8 weeks after acute infection. The patient was prescribed nirmatrelvir/ritonavir to treat SARS-CoV-2 persistence at 3.5 months post-acute infection and observed a reduction in PASC symptoms 3 weeks after completing antiviral treatment. After resurgence of PASC symptoms, she stopped treatment with tocilizumab for rheumatoid arthritis to attempt complete SARS-CoV-2 viral clearance. The severity of the patient’s PASC symptoms subsequently increased, and she developed new-onset brain fog in addition to previous symptoms, which resolved after resumption of tocilizumab treatment. Assessment of adaptive immune responses demonstrated that nirmatrelvir/ritonavir and tocilizumab treatment decreased antiviral and autoreactive T cell activation. After resuming tocilizumab treatment, the patient’s PASC symptoms were significantly reduced, but nasopharyngeal antigen positivity remained. Conclusions: These data suggest that nirmatrelvir/ritonavir should be considered in the treatment of PASC in patients who have SARS-CoV-2 antigen persistence, though care must be taken to monitor the patient for symptom resurgence or viral reactivation. In addition, the IL-6 inhibitor tocilizumab may ameliorate PASC symptoms in patients with persistent headache, fatigue, and brain fog.